Towards the impact of GMC collisions on the star formation rate - Hunter, Glen H.; Clark, Paul C; Glover, Simon; Klessen, Ralf S. (Monthly notices of the Royal Astronomical Society, 2023)
Collisions between giant molecular clouds (GMCs) are one of the pathways for massive star formation due to the high densities created. However, the enhancement of the star formation rate (SFR) is not well constrained. In this study, we perform a parameter study of cloud-cloud collisions and investigate how the resulting SFR depends on the details of set-up. Our parameter study explores variations in collision speed, magnetic field inclination (with respect to the collisional axis), and resolution, as defined by the number of cells per Jeans length. In all our collision simulations, we find a factor of 2-3 increase in the SFR compared to our no collision simulation, with star formation beginning sooner with (a) high collisional velocities, (b) parallel orientation between the magnetic field and collision axis, (c) and lower resolution. The mean virial parameter of high density (and thus possible star-forming) gas increases with collisional velocity, but has little variation with magnetic field inclination. The alignment of the velocity and magnetic field remains uniform in low-density environments but becomes more perpendicular with increasing density, indicating the compression of the magnetic field by collapsing gas. Comparing the trends in the SFR with other GMC collision studies, we find good agreement with studies that account for the gravitational boundedness of the gas in their star formation algorithm, but not with those that simply form stars above a prescribed density threshold. This suggests that the latter approach should be used with caution when modelling star formation on resolved cloud scales.
Vorveröffentlichung: 21 Dezember 2022
Gesehen am 29.03.2023